Peran Mata Kuliah Pendidikan Pancasila sebagai Sarana Pembentukan Karakter Mahasiswa STKIP Citra Bakti - Benediktus Aprianus; Maria Felinsia Mbipi; Maria Yuliana Wulu; Eustakia Mogi; Maria Hildegardis Tandi; Maria Marselina Muja (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Pancasila educatian courses have an important role in shaping the character of students at STKIP Citra Bakti Ngada. This research aims to find out how Pancasila education courses can shape student characters who have integrity, etchis and responsibility towards the Indonesian people and nation. The reseach method used is literature study ( library reseach). In this method, research is carried out by collectingand analyzing data from various literary sources, such as books, scientific journals, articles related to Pancasila education. The results of this reseach show that Pancasila education courses can shape student character through undestanding and practicing Pancasila values. Implementation of Pancasila education courss can be done through contextual approaches, discussions and interactive dialogue, leadership and collaboration practices, preparation of social projects, and assignment of reflections and essays. The results of this research can be used as a reference for improving the effectivenesess of teaching Pancasila education in universities.